Pemanfaatan Media Sosial Sebagai Media Literasi Digital Dalam Pemasaran Produk UMKM Gendang Jimbe - Hidayah, Nurul (UPT Perpustakaan Universitas Bengkulu, 2024)
Social media in today's digital era has become the main thing offered in marketing. One of the choices made by business people as a digital literacy media is product marketing. Relying on digital literacy skills makes social media a lot of potential for the progress of a business. Making the digital literacy skills owned is used in utilizing social media for product marketing. By relying on these abilities, it leads to the convenience and benefits provided by social media in online product marketing. Especially for MSME players who market their products by utilizing social media. MSME players can more easily manage product marketing. Supported by digital literacy skills, the use of social media for product marketing can be online and there are so many benefits. The purpose of this study was to determine the description, obstacles, and support for the utilization of social media in marketing online MSME products of jimbe drum musical instruments. This research uses descriptive qualitative methods. Data collection techniques using interviews, observation, and documentation. Data analysis techniques used data reduction, data presentation, conclusions and verification. Data validity test using triangulation technique. The results of this study are the utilization of social media in online marketing of jimbe drum MSME products as product promotion, as well as communication between sellers and buyers. Obstacles, and support in utilizing social media for online marketing of jimbe drum MSME products are obstacles to internet network problems, and lack of human resources and support in the form of infrastructure such as laptops, cellphones, and several supporting applications.